Effect of In-office Bleaching on Color, Translucency, and Whiteness Variations in CAD-CAM Monolithic Materials - Pena, R. C. [UNESP]; Simoes, R. [UNESP]; Ramos, A. C. [UNESP]; Dovigo, L. N. [UNESP]; Fonseca, R. G. [UNESP] (Operative Dentistry Inc, 2021)
Little is known about the impact of bleaching on the optical properties of computer-aided design and computer-aided manufactured (CAD-CAM) monolithic materials. The aim of the present study was to evaluate the effect of one session of in-office bleaching on stain removal, staining susceptibility, translucency, and whiteness variations of CAD-CAM monolithic materials. Disks were fabricated from Lava Ultimate (LU), Vita Enamic (VE), Vita Suprinity (VS), and IPS e.max CAD (IPS). A spectrophotometer was used to register Commission Internationale de l'Eclairage L*a*b* coordinates. For stain removal, 80 specimens from each material were assessed at baseline (R-0) and after immersion in deionized water or coffee for 36.5 days followed or not by bleaching with 40% hydrogen peroxide (R-1). For staining susceptibility, 80 specimens from each material were analyzed at baseline (R-0'), and after having been bleached or not and immersed in deionized water or coffee (R-1'). Both analyses were calculated as the color difference (Delta E-00) between R-1-R-0 and R-1'-R-0', respectively. Differences in translucency (Delta TP00) and whiteness (.WID) between R-1-R-0 and R-1'-R-0' were also calculated. Data were analyzed by three-way ANOVA and the Games-Howell post hoc test (alpha=0.05). Clinical significance was based on 50%:50% perceptibility and acceptability thresholds for Delta E-00, Delta TP00 and Delta W-ID, respectively. Surfaces were analyzed by scanning electron microscopy. Coffee increased Delta E-00 in LU, VE, and VS, and decreased their translucency and whiteness, whereas the IPS had only its whiteness affected. Bleaching after immersion in coffee decreased Delta E-00 in LU and VE, and increased translucency and whiteness of LU, VE, and VS. No effect was observed on IPS. Bleaching before immersion in coffee decreased translucency of LU, but within the acceptable interval, while VE exhibited lower Delta E-00, and became more translucent and less dark. Both VS and IPS were not affected. One session of in-office bleaching benefited optical properties of the previously stained LU, VE, and VS, without increasing their susceptibility to staining or adversely providing clinically unacceptable variations in their translucency and whiteness. All variations exhibited by the IPS were below the perceptible threshold.